2004
DOI: 10.1177/0148607104028006423
|View full text |Cite
|
Sign up to set email alerts
|

Citrulline Can Preserve Proliferation and Prevent the Loss of CD3 ζ Chain Under Conditions of Low Arginine

Abstract: T cells exhibit the molecular capability of increasing citrulline membrane transport and up-regulating AS expression, thus exhibiting the necessary mechanisms for converting citrulline into arginine and escaping the ill effects of arginine depletion. Therefore, citrulline has the potential to be a substitute for supplemental arginine in diseases associated with arginase-mediated T cell dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
45
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 33 publications
5
45
1
1
Order By: Relevance
“…Additionally, arginase I and iNOS not only compete for arginine but can also inhibit each others activity [26,31,32]. In our experiments, nitrite levels and iNOS expression were up-regulated in PGE 2 stimulated Jurkat cells.…”
Section: Discussionsupporting
confidence: 48%
“…Additionally, arginase I and iNOS not only compete for arginine but can also inhibit each others activity [26,31,32]. In our experiments, nitrite levels and iNOS expression were up-regulated in PGE 2 stimulated Jurkat cells.…”
Section: Discussionsupporting
confidence: 48%
“…In line with this, inhibition of arginase in cultured endothelial cells stimulates NO synthesis (26,27), whereas arginase over-expression inhibits NO synthesis (10). It has been suggested that arginase may modulate or down-regulate NOS activity by substrate competition also in macrophages (28) and T-lymphocytes (29). That arginase had some effect in the present study was clear from the increased mean arterial blood pressure, which presumably reflects a disturbance of NO production in some resistance vessels (6).…”
Section: Discussionsupporting
confidence: 80%
“…In our experiments arginine in growth medium must have been consumed, at least in part, during medium conditioning due to the strong NO formation of the activated microglia. Furthermore, it is known that arginine depletion upregulates Ass (Bansal et al, 2004). Taken together, this could explain the upregulation of Ass by MCM[1]-treated in contrast to MCM[2]-treated astrocytes and could provide a possible mechanism to sustain arginine supply for the generation of NO by microglia.…”
Section: Discussionmentioning
confidence: 96%